PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PEKERJA ALIH DAYA DI PT PERSONA PRIMA UTAMA CABANG YOGYAKARTA - Yuyun Wahyuni; Muhammad Husain Zidni Ar Ridho; R. Suprono Wahyujatmiko (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2022)
Along with the development of the era of competition between companies is also getting tighter. Companies in managing business are required to be able to use all human resources properly and correctly so that company goals can be achieved together. In practice, human resources in a company have varied performance, and are influenced by certain factors. These factors include compensation and work environment. This study aims to: (1) determine the significance of the effect of compensation on the performance of PAD employees at PT. Persona Prima Utama Yogyakarta Branch; (2) determine the significance of the influence of the work environment on the performance of PAD employees at PT. Persona Prima Utama Yogyakarta Branch; and (3) knowing the significance of the simultaneous influence of compensation and work environment on the performance of PAD employees at PT. Persona Prima Utama Yogyakarta Branch.The sample taken is 150 respondents. The instrument test uses validity and reliability tests. Data analysis tool using multiple regression test. Testing the hypothesis using the t test and F test. In addition, to determine the amount of the contribution of the variables entered, the R2 test is carried out.The results of the multiple linear regression equation show that the constant value is 1.599 and the regression coefficient of the compensation variable is 0.191 and the work environment is 0.433. The results of hypothesis testing t and F indicate that the variable compensation and work environment significantly affect the performance of PAD employees at PT. Persona Prima Utama Yogyakarta Branch.